THE IMPORTANCE OF COGNITIVE FEATURES IN TEACHING MEDIA TEXTS TO B2 LEVEL STUDENTS (Journal of Science-Innovative Research in Uzbekistan, 2023)
In today's fast-paced world, media literacy has become a crucial skill for individuals of all ages. As technology advances, the ability to understand, analyze, and critically evaluate media texts is essential. For B2 level students, who have a strong grasp of the English language, incorporating cognitive features in teaching media texts is of paramount importance. Cognitive features not only enhance language skills but also foster critical thinking and analytical abilities. This article explores the significance of cognitive features in teaching media texts to B2 level students and how it empowers them in the digital age